Pengaruh Kualitas E-Service dan Kepuasan Pelanggan pada Perilaku Pelanggan - Albert Ricardo Hanuella; Dini Sari Melati; Jacky; Hela Dixman; Melvin Winata (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The increasing number of online shopping businesses has made competition to dominate the Indonesian market even tougher. Improving service quality is needed to maintain online business. This study aims to examine four variables that have an influence on e-Service quality and the impact that will affect the behavior of a customer. The research was conducted quantitatively by distributing questionnaires to 400 respondents in Batam. The data was analyzed using linear regression through SPSS. Based on the research results, it is known that website design, security / privacy, and fulfillment have a significant influence on e-Service quality with an F value of 104.339 and e-Service quality indirectly has a positive effect on customer behavior. Quality will foster customer satisfaction and trust which encourages repurchase intention, word of mouth, and site revisit. In addition, online shopping service providers need to prioritize website design and fulfillment.